Authoring Autism : On Rhetoric and Neurological Queerness - Yergeau, Melanie, 1984- (Book collections on Project MUSE., 2018)
Challenging the academic and cultural stereotypes that do not acknowledge the rhetorical capabilities of autistic people, Melanie Yergeau shows how autistics both embrace and reject the rhetorical, thereby queering the lines of rhetoric, humanity, agency, and the very essence of rhetoric itself.